1996
DOI: 10.1084/jem.183.4.1587
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Tac (IL2Ralpha): physiology of cell surface shedding and renal catabolism, and suppression of catabolism by antibody binding.

Abstract: SummaryThe interleukin 2 receptor 0t (IL2Rcl; CD25; Tac) is the prototypic model for soluble receptor studies. It exists in vivo as a transmembrane complete molecule (TM-Tac) on cell surfaces and as a truncated soluble form (sTac; slL2Rot), sTac has been used as a serum marker ofT cell activation in immune disorders and of tumor burden in Tac-expressing malignancies. In vivo, serum levels of all soluble proteins depend on the balance between production and catabolism, but little is known about the metabolic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 52 publications
7
43
0
Order By: Relevance
“…However, in two models, a leukaemic cell line which expressed and spontaneously released CD25 and PBMC activated by PHA, we failed to demonstrate a physiological role of MMP-9 in the cleavage of IL-2Ra using a specific inhibitor of MMP-9 at doses up to 800 times the IC50 of the inhibitor. A previous study by Junghans et al also reported that zinc chelators known to inhibit metalloproteinase activity [60] did not influence shedding of sIL-2Ra [61]. The absence of change in sIL-2Ra release in MMP-9-deficient mice also supports these results, as although it does not formally exclude a physiological role of MMP-9 in the regulation of sIL-2Ra, it demonstrates that other proteases may replace MMP-9 for cleavage of sIL2Ra.…”
Section: Discussionsupporting
confidence: 69%
“…However, in two models, a leukaemic cell line which expressed and spontaneously released CD25 and PBMC activated by PHA, we failed to demonstrate a physiological role of MMP-9 in the cleavage of IL-2Ra using a specific inhibitor of MMP-9 at doses up to 800 times the IC50 of the inhibitor. A previous study by Junghans et al also reported that zinc chelators known to inhibit metalloproteinase activity [60] did not influence shedding of sIL-2Ra [61]. The absence of change in sIL-2Ra release in MMP-9-deficient mice also supports these results, as although it does not formally exclude a physiological role of MMP-9 in the regulation of sIL-2Ra, it demonstrates that other proteases may replace MMP-9 for cleavage of sIL2Ra.…”
Section: Discussionsupporting
confidence: 69%
“…Our work with animal models showed that Tac is catabolized rapidly in vivo by mainly renal mechanisms, and this catabolism is delayed markedly by antibody binding with no impact on survival of the antibody itself (10). Therefore, the progressive decline of antibody bioactivity in these patients implies a continued production of antigen during therapy that can be judged by the time course of the bindability change.…”
Section: Resultsmentioning
confidence: 94%
“…k Ï­ ln2͞t 1͞2 is the antibody beta phase rate constant for IgG, which is undisturbed by antigen binding (10) and provisionally is assigned also as the clearance rate constant for antigen bound to antibody. A 0 and B 0 are moles of A and B at time Ï­ 0. q, the sTac production rate, is selected to provide the best fit of the data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 was subjected to HPLC analyses. The amount of radioactivity in each fraction was plotted for mice receiving -----------------------lism of sIL-2Rα, 48) in which administration of anti-Tac to mice with increased sIL-2Rα levels in serum resulted in longer retention of the sIL-2Rα, but did not decrease the half-life of the anti-Tac IgG. Furthermore, in our previous study we demonstrated that preinjection of HuTac resulted in formation of complexes with sIL-2Rα that competed with and prevented the binding of the radiolabeled dsFv to sIL-2Rα.…”
Section: Discussionmentioning
confidence: 99%